Keanekaragaman Jenis Amfibi Ordo Anura Di Hutan Adat Datuk Rangkayo Mulio Kabupaten Bungo Provinsi Jambi: Diversity of amphibian species of the order Anura in the Datuk Rangkayo Mulio Customary Forest, Bungo Regency, Jambi Province - Aini, Yasri Syarifatul; Bangun, Zefanya Alfa Permana; Albayudi, Albayudi; Nugraha, Anggit Prima; Darsono, Beti Septiana; Nur’aini, Hanifah (Fakultas Kehutanan Universitas Jambi, 2026)
ABSTRACT Anurans play an important ecological role in maintaining ecosystem balance and are widely recognized as bioindicators of environmental quality due to their sensitivity to habitat changes. Information on anuran diversity in customary forests of Jambi Province remains limited. This study aimed to identify anuran species, analyze community structure, and describe environmental conditions in the Datuk Rangkayo Mulio Customary Forest, Bungo Regency, Jambi Province, Indonesia. Field surveys were conducted from July to August 2024 using the Visual Encounter Survey (VES) method with two repeated surveys along each transect. Captured individuals were temporarily marked to prevent double counting during the sampling period. Community structure was analyzed using the Shannon–Wiener diversity index, Margalef species richness index, and Pielou evenness index, while environmental variables included air temperature, air humidity, water temperature, and water pH. A total of 95 individuals representing 16 species from six families (Bufonidae, Dicroglossidae, Ranidae, Rhacophoridae, Microhylidae, and Megophryidae) were recorded. Ranidae was the most abundant family, whereas Chalcorana parvaccola was the dominant species. The community exhibited a moderate diversity index (H' = 2.397), low species richness (Dmg = 3.294), and high evenness (E = 0.864). Environmental measurements ranged from 24.1–26.6 °C for air temperature, 79–95% for air humidity, 26–30 °C for water temperature, and pH 5.91–6.35. These findings indicate that the Datuk Rangkayo Mulio Customary Forest continues to support a relatively stable anuran community. The results provide baseline biodiversity information that can be used to support long-term monitoring and community-based management and conservation of customary forests. Keywords: anura, community structure, customary forest, diversity, visual encounter survey. ABSTRAK Amfibi Ordo Anura merupakan kelompok vertebrata yang berperan penting dalam menjaga keseimbangan ekosistem dan berfungsi sebagai bioindikator kualitas lingkungan karena sensitif terhadap perubahan habitat. Informasi mengenai keanekaragaman amfibi pada kawasan hutan adat di Provinsi Jambi masih terbatas, sehingga penelitian ini bertujuan mengidentifikasi jenis Anura, menganalisis struktur komunitas, serta mendeskripsikan kondisi faktor lingkungan di Hutan Adat Datuk Rangkayo Mulio, Kabupaten Bungo, Provinsi Jambi. Penelitian dilaksanakan pada Juli–Agustus 2024 menggunakan metode Visual Encounter Survey (VES) dengan pengulangan jalur sebanyak dua kali. Individu yang ditemukan diberi penandaan sementara (temporary individual marking) untuk mencegah penghitungan ganda selama survei. Data dianalisis menggunakan indeks keanekaragaman Shannon-Wiener, indeks kekayaan jenis Margalef, dan indeks kemerataan Pielou, serta didukung oleh pengukuran suhu udara, kelembapan udara, suhu air, dan pH air. Hasil penelitian memperoleh 95 individu yang terdiri atas 16 jenis dari 6 famili, yaitu Bufonidae, Dicroglossidae, Ranidae, Rhacophoridae, Microhylidae, dan Megophryidae. Famili Ranidae merupakan famili dengan jumlah individu terbanyak, sedangkan Chalcorana parvaccola menjadi jenis yang paling dominan. Nilai indeks keanekaragaman tergolong sedang (H' = 2,397), indeks kekayaan jenis tergolong rendah (Dmg = 3,294), dan indeks kemerataan tergolong tinggi (E = 0,864). Suhu udara berkisar 24,1–26,6 °C, kelembapan udara 79–95%, suhu air 26–30 °C, dan pH air 5,91–6,35. Hasil penelitian menunjukkan bahwa Hutan Adat Datuk Rangkayo Mulio masih mendukung keberadaan komunitas amfibi dengan distribusi individu yang relatif merata. Data ini dapat menjadi informasi dasar (baseline) untuk pemantauan biodiversitas serta mendukung pengelolaan dan konservasi hutan adat berbasis masyarakat. Kata kunci: anura, hutan adat, keanekaragaman, struktur komunitas, visual encounter survey.